Y2O3:Eu3+ concentration and particle size: their impacts on color rendering index and lumen of multi-chip white diodes - Phuc Dang Huu; Phan Xuan Le (Institute of Advanced Engineering and Science, 2022)
Aiming at achieving higher colour standard for multi-chip white light-emitting diode (MCW-LEDs) through the enhancement of their color rendering index (CRI), this article worked on and proposed a novel MCW-LED package using a compound of red phosphor Y2O3:Eu3+. The red phosphors were synthesized and applied to build both protective coating and in-cup phosphor configurations. The CRI of MCW-LED which has high correlated colour heat of 8,500 K was observed to be heightened to 86. Moreover, the scattering of the light when added the red phosphor Y2O3:Eu3+ is demonstrated using Mie-scattering theory, while the influences of the red-light enhancement is analyzed using the law of Lambert-Beer.